Odpowiedź :
Oblicz.
a) [tex](-4)^2 + 2^3 = 16 + 8 = 24[/tex]
d) [tex]8^2 - (-4)^3 = 64 + 64 = 128[/tex]
b) [tex]3^2 - 5^2 = 9 - 25 = - 16[/tex]
e) [tex]-4^2 + (-3)^4 = 16 + 81 = 97[/tex]
c) [tex](-4)^3 - 6^2 = -64 - 36 = -100[/tex]
f) [tex](-1)^7 - (-2)^6 = -1 - 64 = -65[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
a) (-4)²+2³= 16+2³=16+8+24
d) 8²-(-4)³=64-(-4)³=64-(-64)=64+64=128
b) 3²-5²=9-5²=9-25= -16
e) -4²+(-3)⁴=-16+(-3)⁴=-16+81=65
c) (-4)³-6²=-64-6²=-64-36=-100
f) (-1)⁷-(-2)⁶=-1-(-2)⁶=-1-64=-65
Raczej jest wszystko dobrze! :D